Analysis of strained microfabrics in the "Porfidos Rioliticos". Basement area of Pigüe, Sierras Australes de Buenos Aires - Japas, M.S. (1998)
knowledge of the initial shape of strain markers allows calculation of the strain ellipsoid (axial relationships and orientation) when they show distorted geometries after deformation. This information is usually combined with the analysis of other micro- and mesostructures that constitute the dynamic framework in which the whole assemblage of structures developed. If only one deformational episode was responsible for all of them, the result is a highly coherent picture. In this paper, the quantification of strain and orientation of strain axes, is attempted on the basis of distorted hexagonal columns cropping out close to Puesto El Malabar (Pigüé, Sierras Australes de Buenos Aires). This columnar strucutre occurs in rhyolitic flows and tuffs of the Precambrian (?) basement in the area. It is apparent from this study that deformation in the central part of the north-western arc of Sierras Australes is markedly heterogeneous at all scales, with axial relationships giving values that record a variationin between almost no deformation and belts of high strain in which cleavage erases all evidence of columnar jointing. Micro- and mesostructural analysis shows dextral simple shear in plan view, oriented Az.145°-150° , and E-W stripes of sinistral shear that appear to be later and fewer than the earlier, one. Evidence of shear to the NE in vertical section has been found that is also heterogeneously developed. Secondary microstructures also show geometric relationships that are coherent with the general picture in the area. The regional significance of these data is analyzed in the regional picture, and it is concluded that it fits the previous model of an arcuate belt resulting from local development of conjugate megashears, with E-W (sinistral) and SW-NE (dextral) bands shaping the arc. © 1998 Asociación Geológica Argentina.